The influence of digital storytelling on story writing skills of class II elementary school students - Nuroh, Ermawati Zulikhatin; Frestiya Adiyawati , Fany (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This study aims to determine the presence or absence of Digital Storytelling on the Story Writing Skills of Class II Elementary School Students. This study used a quantitative approach. This type of research is pre-experimental design with the one group pretest posttest design method. The sample is 25 students. The instrument is a test in the form of an essay question. The results obtained are sig. (2-tailed) (0.00) < 0.05 means that Ha is accepted and Ho is rejected. So it can be concluded that Digital Storytelling in writing stories for class II students can influence students' writing skills for the better. As for the value of how much influence is received, a value of 0.76 is obtained. This value is greater than criteria table, which is 0, 14 so it is stated that the use of Digital Storytelling has a great influence on the story writing skills of class II elementary school students. It is hoped that the results of this study can provide knowledge and insight about other learning innovations in the ability to write stories for future researchers.